Design and Implementation of an End-to-End IoT System for Smart Healthcare (Journal of Engineering, 2025)
In recent years, there has been exponential growth in the Internet of Things (IoT) in various sectors, especially healthcare. The traditional healthcare sector has faced several challenges, such as poor health services, crowding and queuing at medical centers, and manual searches for or missing patient records; a smart health system is needed to overcome these challenges. This study presents the design and implementation of end-to-end IoT architecture, which is built by the integration of various open-source technologies. The pulse care system is implemented using Node.js and React.js, which offer features such as electronic health records (EHR), smart appointments, prescription documentation, and health monitoring. Additionally, various users (admin, patient, doctor, and pharmacist) communicate using a user-friendly graphical interface. In terms of a wearable device, it allows visualization of all the data generated by the sensors in real time (heart rate, body temperature, and blood oxygen). The ESP32 is used as a microcontroller that communicates via its built-in Wi-Fi with the MQTT Mosquitto broker. Standard IoT protocols, Message Queuing Telemetry Transport (MQTT) and Hypertext Transfer Protocol (HTTP), are used. The broker's performance is evaluated in terms of average latency at various QoS levels and with the increase in the number of concurrent users. The results of the experiment demonstrate how important it is to choose the appropriate QoS level based on the requirements of the application. Furthermore, the proposed system's data rate is roughly 3.07 kb/s, which is considered low and suitable for sending small data via any wireless method.